Antagonistic reaction of Leptosphaeria sp. and Neocardana musae against several tree pathogens - Mohamad Bahtiar, Nur Ainaa Nabilah (2019)
The use of endophytic fungi that are able to inhibit growth of tree pathogens is an alternative to fungicide utilization. In this study, the growth performance of fungal endophytes (Leptosphaeria sp. and Neocardana musae) and fungal pathogens (Ceratocystis fimbriata, Phellinus noxius and Fusarium oxysporum) on Potato Dextrose Agar (PDA) were examined. The antagonistic activities of the two selected endophytes were evaluated using dual culture and non-volatile compound assays. The growth of Fusarium oxysporum was 3-fold faster compared to Ceratocystis fimbriata when grown in medias without endophytes. However, the radial growth of Fusarium oxysporum was two times slower then Leptosphaeria sp. in non-volatile compound assay. In dual culture assay, Leptosphaeria sp. had the highest potential of antagonistic inhibition against Fusarium oxysporum while in non-volatile compound assay Neocardana musae had the highest potential of antagonistic inhibition against Phellinus noxius. Positive percentage of inhibition of both endophytes in dual culture assay against Fusarium oxysporum was between 30-48% while Phellinus noxius was between 11-22% on day seven. Meanwhile, the positive percentage of inhibition in non-volatile compound assay after seven days for the three tree pathogens against two endophytes were between 4-32%. Both selected endophytes had potential antagonism effect against the three tree pathogens. This study was limited to artificial surrounding. Further study needs to be carried out to confirm endophytic fungi as natural biocontrol agents against tree diseases.